Aiming for the Sweet Spot: Glyco-Immune Checkpoints and γδ T Cells in Targeted Immunotherapy - Bartish, Margarita; del Rincón, Sonia V.; Rudd, Christopher E.; Saragovi, H. Uri (Frontiers in Immunology, 2020)
Though a healthy immune system is capable of recognizing and eliminating emergent cancerous cells, an established tumor is adept at escaping immunosurveillance. Altered and tumor-specific expression of immunosuppressive cell surface carbohydrates, the so-called tumor glyco-code, is a prominent feature of transformed cells and is recognized as one of the mechanisms by which tumors escape anti-tumor immunity. Given their persistent and homogeneous expression, tumor-associated glycans are a promising target for clinical translation both as biomarkers and targets in immunotherapy. However, uncovering their full potential has been a challenge due to their low immunogenicity and strong immunosuppressive properties. γδ T cells are a small but potent subclass of circulating T cells, with the capacity for MHC-unrestricted antigen recognition and inherent anti-tumor properties, whose capacity for therapeutic exploitation is becoming increasingly apparent. In this review, we discuss the interaction between tumor-associated glycans and anti-tumor immunity, with an emphasis on the potential of γδ T cells in targeting the tumor glyco-code. Understanding the many facets of this interaction holds the potential in unlocking new ways to make use of both tumor-associated glycans and γδ T cells for therapeutic intervention.